PERAN PEMERINTAH MELINDUNGI USAHA RITEL TRADISIONAL DALAM PANDANGAN HUKUM EKONOMI SYARIAH - Najwan Fabian; Rabiatul Adawiyah; Fajrul Ilmi; Muhammad Syarif Hidayatullah (Mitsaqan Ghalizan, 2023)
This study aims to determine the role of the Banjarmasin city government in protecting traditional retail businesses and to analyze it in view of sharia economic law and also to find out the obstacles faced by the Banjarmasin city government in protecting traditional retail businesses. This research is a field research (field research) with a qualitative approach and using interviews and documentation methods. The results of research conducted by researchers indicate that the government has protected traditional retail businesses in the city of Banjarmasin, so that they continue to run well, several ways are carried out by providing services provided by the government, namely conducting guidance to business actors in work programs and also facilitating by providing capital assistance by the principle of cooperation and the principle of interest-free money loans through banks that have collaborated with the Banjarmasin City Cooperative Service. So in the view of sharia economic law, the loan should be interest-free, because it is a qardh contract that is social in nature where the existence of interest makes it a ribawi transaction. Then the obstacles faced by the Banjarmasin City government in protecting traditional retail businesses lie in the lack of ASN human resources which will have an impact on reducing the composition of the resulting performances, lack of data from the traditional retail business actors themselves, most traditional retail business actors are aged and business actors who are not intend to move forward.